Kesejarahan Hadis dalam Tinjauan Teori Common Link - Rahmadi Wibowo Suwarno (Jurnal Living Hadis, 2018)
This study entitled Kesejarahan Hadis Tinjauan Teori Common Link. The background of the study is study of authenticity, origin, and history of hadith has become an interesting topic and even a debate from the beginning of Islam until now. Interesting and a debate because it concerns the authenticity of Islamic teachings. Among the new theories and worldviews in contemporary criticism of contemporary hadith are the common link theory. For it is formulated the purpose of this study is to find out how to work and understand the implications of the theory of common links to the historic Hadith of the Prophet. The results of this study indicate that the common link theory impacts on the source or origin of hadith based on whom. Differences in interpreting common links determine which hadith comes from whom. Penelitian ini berjudul "Kesejarahan Hadis Hadiah Teori Common Link". Latar belakang penelitian untuk mengetahui keaslian, asal, dan sejarah hadis telah menjadi topik yang menarik dan bahkan menjadi perdebatan sejak awal Islam hingga sekarang. Menarik dan menjadi perdebatan karena menyangkut keaslian ajaran Islam. Di antara teori-teori baru dan pandangan dunia dalam kritik kontemporer hadis  adalah teori common link. Oleh karena itu dirumuskan tujuan dari penelitian ini adalah untuk mengetahui bagaimana cara kerja dan memahami implikasi dari teori common link dengan historisitas hadis Nabi. Hasil penelitian ini menunjukkan bahwa teori common link berdampak pada sumber atau asal-usul hadis yang didasarkan pada siapa (rawi atau nabi). Perbedaan dalam menafsirkan common link menentukan sebuah hadis berasal dari siapa.